Photoexcited Nitroarenes as Anaerobic Oxygen Atom Transfer Reagents - Wise, Dan E.; Parasram, Marvin (Synlett, 2023)
Applications of photoexcited nitroarenes have been underdeveloped in organic synthesis. Since early reports on the direct excitation of nitroaromatics with harsh UV light, these synthetically useful reagents have not been tamed for use in modern synthetic chemistry. We have developed practical synthetic protocols for the anaerobic oxidation of hydrocarbon substrates using commercially available nitroarenes as photochemically activated oxidants under visible light. Using this approach, a wide variety of olefins are anaerobically cleaved to their corresponding carbonyls, and aliphatic C–H bonds are hydroxylated to give alcohols. The anaerobic reaction conditions enable oxidatively sensitive functional groups to be tolerated and the employment of visible light makes this method highly sustainable. Mechanistic studies support that the photoexcited nitroarene biradical intermediate is responsible for the oxygen atom transfer events.1 Introduction2 Alkene Cleavage Promoted by Photoexcited Nitroarenes3 Photoinduced Nitroarene-Mediated C–H Hydroxylation4 Conclusions
Keywords: photochemistry; nitroarenes; biradical; cleavage of alkenes; olefins; carbonyl; C–H hydroxylation; anaerobic oxidation